A preparation method and application of nitrogen-oxygen doped porous carbon for supercapacitors based on cistanche residue
Patent Information
- Application Number
- CN202410293281.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-14
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-03-14
AI Technical Summary
In existing technologies, the residue of traditional Chinese medicine is directly discarded, resulting in waste and pollution, and its potential in the energy field is not effectively utilized, especially in the preparation of electrode materials for supercapacitors.
Using Cynomorium songaricum residue as a carbon source, combined with KOH as an activator and melamine as a nitrogen source dopant, nitrogen-oxygen-doped porous carbon electrode materials were prepared through low-temperature pre-activation and high-temperature carbonization.
The prepared porous carbon material has a high specific surface area and abundant N and O content. As an electrode material, it exhibits high capacity and stability, opening up a high-value utilization pathway for waste biomass resources and reducing environmental pollution.
Smart Images

Figure CN118183735B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of energy technology, specifically relating to a method for preparing nitrogen-oxygen-doped porous carbon for supercapacitors based on Cynomorium songaricum residue and its application. Background Technology
[0002] With rapid economic development and increasing public awareness of environmental issues, reducing carbon emissions and developing clean and efficient energy storage devices have become a global consensus. Supercapacitors, as a novel energy storage device, have broad application prospects due to their advantages of high power density, fast charge / discharge rates, good rate performance, and long cycle life. Electrodes are the core component of supercapacitors, directly determining the device's electrochemical performance. Among numerous electrode materials, biomass-derived carbon materials are considered important candidate materials for electrochemical double-layer capacitors due to their abundant reserves and carbon content, unique natural structure, tunable pore structure, low cost, and environmental friendliness.
[0003] Traditional Chinese medicine (TCM) is a unique and rich biomass material that has played a vital role in combating diseases for thousands of years. However, the extraction of active ingredients from TCM generates a large amount of residue (60-70 million tons / year), most of which is directly discarded, causing enormous waste and pollution. Therefore, exploring green and efficient methods for utilizing TCM residue is of great significance for the recycling of TCM resources and environmental protection.
[0004] Cynomorium songaricum is an important traditional Chinese medicine containing flavonoids, steroids, terpenes, organic acids, glycosides, and tannins. It is rich in elements such as carbon, nitrogen, and oxygen, providing a stable carbon source. Furthermore, approximately 4,000 tons of Cynomorium songaricum raw materials are used annually, resulting in a large amount of residue. Therefore, the recycling of these valuable wastes has great potential, especially in the energy sector. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings and deficiencies of the existing technology and to provide a method for preparing nitrogen-oxygen-doped porous carbon for supercapacitors based on Cynomorium songaricum residue and its application.
[0006] The technical solution adopted in this invention is as follows: A method for preparing nitrogen-oxygen-doped porous carbon for supercapacitors based on Cynomorium songaricum residue, comprising the following steps: (1) Wash the dregs of Cynomorium songaricum, dry them, slice them, and then grind them into powder using a grinder; (2) Pre-carbonize the residue powder of Cynomorium songaricum under an inert gas; (3) The cynomorium dregs powder treated in step (2) is mixed with KOH and melamine and ball-milled to obtain a mixture; (4) Under the protection of inert gas, the mixture of step (3) is carbonized at high temperature, cooled to room temperature, and the product is washed with HCl and deionized water until neutral, and dried to obtain nitrogen-oxygen doped porous carbon for supercapacitors.
[0007] Furthermore, in step (1), the mesh size of the Cynomorium songaricum powder is 100 mesh.
[0008] Furthermore, in step (1), the drying temperature is 105°C.
[0009] Furthermore, in step (2), the Cynomorium songaricum powder is heated at a rate of 5°C / min. -1 The temperature was raised to 300℃ and pre-carbonized for 2 hours under a nitrogen flow.
[0010] Furthermore, in step (3), the weight ratio of Cynomorium songaricum powder to KOH and melamine is 1:1:0.5.
[0011] Furthermore, in step (4), the inert gas is nitrogen.
[0012] Furthermore, in step (4), the high-temperature carbonization is performed at 800°C for 2 hours.
[0013] This invention uses *Cistanche deserticola* residue as a carbon source, KOH as an activator, and melamine as a nitrogen source, dopant, and auxiliary activator to prepare electrode materials for supercapacitors using a low-temperature pre-activation and high-temperature carbonization method. The raw materials for this invention are waste materials, the preparation process is simple, and the obtained porous carbon material has a large specific surface area and is rich in N and O. As an electrode material, it has a stable structure and high capacity and stability. This invention not only opens up a new way to convert waste biomass into high-value-added products but also provides a new solution for reducing environmental pollution. Attached Figure Description
[0014] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, obtaining other drawings based on these drawings without creative effort still falls within the scope of the present invention.
[0015] Figure 1 These are SEM images of Embodiment 1 (A) and Embodiment 2 (B) of the present invention under a 10x magnification lens; Figure 2 These are SEM images of Embodiment 3 (A) and Comparative Example (B) of the present invention under a 10x magnification lens; Figure 3 These are TEM images of Embodiment 1 of the present invention under 20 (A) and 200 (B) magnification. Figure 4 These are the adsorption / desorption isotherms (A) and pore size distribution diagrams (B) of Embodiments 1, 2, 3 and the comparative examples of the present invention. Figure 5 These are the XPS full spectra (A) of Examples 1, 2, and 3 and the comparative example of the present invention, as well as the C, N, and O spectra (B)-(D) of Example 1; Figure 6 These are the cyclic voltammetry diagrams (three-electrode system) of Embodiments 1, 2, 3 and the comparative example of the present invention. Figure 7 These are constant current charge-discharge diagrams (three-electrode system) for Embodiments 1, 2, 3 and the comparative example of the present invention. Figure 8 These are the rate performance diagrams (three-electrode system) of Embodiments 1, 2, 3 and the comparative example of the present invention. Figure 9 These are the electrochemical impedance diagrams (three-electrode system) of Examples 1, 2, 3 and the comparative example of the present invention. Figure 10 This is the cyclic voltammogram of Example 1 at different scan rates (three-electrode system); Figure 11 This is a constant current charge-discharge diagram of Example 1 under different current densities (three-electrode system). Figure 12 This is a cyclic stability diagram of the three-electrode system in Example 1; Figure 13 The diagram shows the cyclic stability of the two-electrode system in Example 1. Detailed Implementation
[0016] To make the objectives, technical solutions, and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings.
[0017] Example 1 (1) Wash the dregs of Cynomorium songaricum, dry them, crush them into fine particles, pass them through a 100-mesh filter, and dry them overnight in an oven at 105°C. The dregs of Cynomorium songaricum described in this embodiment are collected from the dregs extracted from pharmacies, or from the dregs extracted by decoction three times. (2) The pretreated Cynomorium powder in step (1) was placed in a tube furnace and pre-carbonized under nitrogen flow at a temperature of 300℃ for 2 h and a heating rate of 5℃ / min. (3) The pre-carbonized product from step (2) is mixed with KOH and melamine (weight ratio 1:1:0.5) and ball-milled. (4) Using a tube furnace, the mixture after ball milling in step (3) is carbonized under nitrogen protection at a temperature of 800℃ for 2 hours at a heating rate of 5℃ / min, and then naturally cooled to room temperature. (5) The product obtained in step (4) is treated with 1 mol L-1 Wash with HCl and deionized water until neutral, and dry at 80°C to obtain product CSC-0.25.
[0018] Example 2 (1) The product in step (2) of Example 1 was mixed with KOH and melamine (weight ratio 1:1:0.25) and ball-milled; the conditions of the remaining steps remained unchanged, and the product CSC-0.5 was obtained.
[0019] Example 3 (1) The product in step (2) of Example 1 was mixed with KOH and melamine (weight ratio 1:1:0.75) and ball-milled; the conditions of the remaining steps remained unchanged, and the product CSC-0.75 was obtained.
[0020] Comparative Example Without adding melamine in step (3) of Example 1, the procedure was continued according to steps (4) and (5) of Example 1 to obtain product CSC-0.
[0021] Microscopic characterization: Figure 1 Examples 1 and 2 (CSC-0.5, CSC-0.25) are examples. Figure 2 The images shown are scanning electron microscope (SEM) images of Example 3 and the comparative examples (CSC-0.75, CSC-0). It can be seen that due to the activating effect of potassium hydroxide, the material surfaces of all four samples exhibit a porous structure. However, in the first three samples where melamine was present, the sample surfaces were more porous and rougher, with a greater variety of pore sizes. This is mainly because melamine, in addition to acting as a nitrogen source, can also act as an auxiliary activator, interacting with the material and decomposing into substances such as NH3, C2N2, C3N3, and C3N2. + These nitrogen-containing substances can etch carbon, creating tiny pores.
[0022] Figure 3 This is a transmission electron microscope image of Example 1 (CSC-0.5). A large number of white dots can be observed in the image, which indicates the presence of a large number of micropores in Example 1.
[0023] Figure 4 The adsorption / desorption isotherms and pore size distribution diagrams for Example 1 (CSC-0.5), Example 2 (CSC-0.25), Example 3 (CSC-0.75), and Comparative Example (CSC-0) are shown in Table 1. Their specific surface area and pore size data are also shown in Table 1.
[0024] Table 1. Specific surface area and pore volume values of four samples from Figure 4As shown in Table 1, the specific surface area of the comparative sample, obtained only with pre-carbonization and potassium hydroxide activation without the addition of melamine, was 1712.9 m². 2 g −1 In contrast, Examples 1-3 exhibited higher N2 adsorption capacity, demonstrating type I isothermal characteristics of microporous materials. The specific surface area distribution ranged from 1839.1 to 2448.0 m². 2 g −1 The pore volume ranges from 0.9395 to 1.2410 cm³. 3 g −1 This indicates that melamine plays a synergistic role in the pre-carbonization and potassium hydroxide activation processes, demonstrating its advantage in increasing specific surface area.
[0025] As can be seen from Table 1, compared with Examples 2 and 3, the specific surface area of Example 1 (2894 m²) is significantly larger. 2 g -1 ) and total pore volume (1.241 cm) 3 g -1 The results showed that the melamine content was the highest. This is because when the ratio of melamine to carbon material is 0.25, the etching effect of melamine on the material is insufficient, resulting in a smaller pore size and specific surface area. However, if melamine is excessively doped (CSC-0.75), the pores collapse, leading to a reduction in specific surface area and pore volume. Scanning electron microscopy observations also confirmed this result. These results indicate that an appropriate amount of melamine is crucial for synthesizing carbon materials with high specific surface area and porous structures. Porous materials with high specific surface area can provide shorter transport paths for ions and sufficient electrode-electrolyte interfaces, effectively improving the migration rate of electrolyte ions and benefiting electrochemical processes.
[0026] Table 2. Elemental distribution of C, N, and O in the four samples Figure 5 The full X-ray photoelectron spectroscopy spectra of Examples 1 (CSC-0.5), 2 (CSC-0.25), 3 (CSC-0.75), and Comparative Example (CSC-0) are shown, along with the C, N, and O spectra of Example 1. From... Figure 5 As shown in Table 2, the nitrogen (N) content in the samples gradually increased with the increase of melamine dosage, indicating that the addition of melamine can increase the nitrogen content in the samples. Example 3 showed the highest N content (more than five times that without melamine), confirming the formation of N / O co-doped porous carbon materials. The introduced melamine not only acts as an auxiliary activator but also provides a nitrogen source. The presence of oxygen- and nitrogen-containing functional groups effectively improves the wettability of the electrode material and provides additional active sites and pseudocapacitance, making this material a promising electrode material.
[0027] Electrochemical performance testing: Figure 6 Examples 1 (CSC-0.5), 2 (CSC-0.25), 3 (CSC-0.75), and the comparative example (CSC-0) were tested in a three-electrode system. Figures 6-12 The cyclic voltammetry (CV) curves obtained under a three-electrode system (electrolyte: 6MKOH) show good rectangular shapes with prominent broad peaks. This indicates that the specific capacitance of the capacitor is mainly composed of the electric double-layer capacitance (EDLC) contributed by the high specific surface area and the partial pseudocapacitance introduced by the N and O functional groups on the sample surface. Example 1 shows the largest rectangular area.
[0028] Figure 7 The figures show the galvanostatic charge-discharge curves (electrolyte: 6M KOH) for Examples 1 (CSC-0.5), 2 (CSC-0.25), 3 (CSC-0.75), and the comparative example (CSC-0). The curves exhibit a typical triangular shape, indicating good double-layer capacitance performance. At 1 A g... −1 The specific capacitance at each location is 369.3 F g. −1 322.4 F g −1 268.0 F g −1 and 250.9F g −1 Among them, the capacitance value of Example 1 is the largest.
[0029] Figure 8 The electrochemical impedance spectroscopy (Electrolyte: 6M KOH) plots for Examples 1 (CSC-0.5), 2 (CSC-0.25), 3 (CSC-0.75), and the comparative example (CSC-0) are shown. The semicircle diameter and intercept of Example 1 are much smaller than those of the comparative example, indicating that Rs and Rct of Example 1 are lower than those of the comparative example. The Rct and Rs of CSC-0.5 are 0.09 Ω and 0.47 Ω, respectively. Other parameters are shown in Table 3. Table 3 Electrochemical impedance values of four samples Figure 9 This is a rate performance graph for Example 1 (CSC-0.5), Example 2 (CSC-0.25), Example 3 (CSC-0.75), and Comparative Example (CSC-0) (electrolyte: 6M KOH). As can be seen from the graph, CSC-0.5 exhibits better rate performance at current densities of 1, 2, 5, 10, 20, 30, 50, 80, and 100 A g. -1The specific capacitances at the following times were 369.3, 317.74, 280.43, 260.87, 241.74, 224.35, 213.04, 187.82, and 173.91 F g, respectively. -1 , at 100 A g -1 The capacitance retention rate was 47.09%, indicating that the sample of Example 1 has good characteristics and rate performance.
[0030] Figure 10 These are cyclic voltammograms of Example 1 at different scan rates. It can be seen that at a high scan rate of 400 mV / s... -1 The curve remains approximately a symmetrical rectangle, indicating that the electrode exhibits ideal electrochemical capacitance behavior.
[0031] Figure 11 The images show the galvanostatic charge-discharge curves of Example 1 at different current densities. The GCD curves of this material maintain their shape well, indicating good rate stability. Calculations were performed at 1 A g... -1 At that time, the specific capacitance was 369.3 F g. −1 However, when the current density increases to 100 A g −1 At that time, the specific capacitance value was still 173.91 F g. -1 Its capacitance retention rate is as high as 47.1%. This indicates that the material still has a high specific capacitance and a high capacitance retention capability even at high current densities.
[0032] Figure 12 This is for the cycling stability of Example 1. The electrode material of Example 1 exhibits good long-term stability. At a current density of 10 A g... −1 In this case, the capacitance of the electrode remains at 94.33% during 22,000 charge-discharge cycles.
[0033] Figure 13 This demonstrates the two-electrode cycle stability of Example 1. The electrode materials from Example 1, when assembled into a symmetrical supercapacitor, exhibit good long-term stability. At a current density of 10 A g... −1 In this case, the capacitance of the electrode remains at 96.08% during 60,000 charge-discharge cycles, with a decay of less than 4%.
[0034] While the invention has been described with reference to several specific embodiments, it should be understood that the invention is not limited to the disclosed specific embodiments. The invention is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.
[0035] The above description discloses only preferred embodiments of the present invention and should not be construed as limiting the scope of the present invention. Therefore, equivalent variations made in accordance with the claims of the present invention are still within the scope of the present invention.
Claims
1. A method for preparing nitrogen-oxygen-doped porous carbon for supercapacitors based on Cynomorium songaricum residue, characterized in that... Includes the following steps: (1) Wash the dregs of Cynomorium songaricum, dry them, crush them into fine particles, pass them through a 100-mesh filter, and dry them overnight in an oven at 105°C; the dregs of Cynomorium songaricum are collected from the dregs extracted from pharmacies, or from the dregs extracted by decocting them three times in water. (2) The pretreated Cynomorium powder in step (1) was placed in a tube furnace and pre-carbonized under nitrogen flow at a temperature of 300℃ for 2 h and a heating rate of 5℃ / min. (3) The pre-carbonized product from step (2) is mixed with KOH and melamine in a weight ratio of 1:1:0.5 and ball-milled. (4) Using a tube furnace, the mixture after ball milling in step (3) is carbonized under nitrogen protection at a temperature of 800℃ for 2 hours at a heating rate of 5℃ / min, and then naturally cooled to room temperature. (5) The product obtained in step (4) is washed with 1 mol L-1 HCl and deionized water until neutral, and dried at 80°C to obtain the product nitrogen-oxygen doped porous carbon for supercapacitors.
Citation Information
Patent Citations
Porous carbon material with high specific surface area and high yield as well as auxiliary activation preparation method and application thereof
CN113213474A
